ANALISIS PEMBIAYAAN PERBANKAN SYARIAH DI INDONESIA PERIODE 2010 – 2018 - Shalihul Aziz Widya Iriawan; Milkhatin Nikmah (Jurnal Dinamika Ekonomi & Bisnis, 2019)
This study aims to analyze whether Sharia Bank Indonesia Certificates and third party funds have a significant effect on Sharia banking financing for the period 2010 - 2018. This research is a quantitative study, with samples of Sharia Banking Quarterly Financial Statements for the period 2010 - 2018. The type of data used is secondary data from Bank Indonesia sharia banking statistics. The analytical method used is multiple linear regression, the classic assumption test, and the hypothesis test (F test and t test), the analytical tool used is SPSS V20. The results showed that Bank Indonesia Sharia Certificates had no significant effect on Sharia Banking Financing, while Third Party Funds had a significant effect on Sharia Banking Financing. Simultaneously SBIS and DPK have a significant effect on Sharia Banking Financing for the period 2010 - 2018. With these findings, Sharia Banking is advised to be cautious in conducting financing so that the level of risk of non-performing financing can be minimized, besides that Islamic Banking must maintain liquidity and fund stability if At any time funds are taken by customers as third parties, banks are still able to maintain liquidity emissions in Indonesia.